Cytomegalovirus Infection in the Era of Preemptive Strategy in Allogeneic Hematopoietic Cell Transplant Recipients: Progression From Viremia to Disease Remains Rare But Unpredictable. Issue 1 (January 2019) - Obeid, Karam M.; Cober, Eric; Abounader, Donna; Gerds, Aaron T.; Mossad, Sherif B.
Abstract : Objective: The aim of this study was to describe our experience with, and identify risk factors associated with, breakthrough cytomegalovirus disease (CMVD) in allogeneic hematopoietic stem cell transplant during regular monitoring and preemptive therapy for CMV viremia. Methods: This was a retrospective study comparing allogeneic hematopoietic stem cell transplant recipients who developed CMVD despite a preemptive treatment strategy to patients with CMV viremia without CMVD. Results: Of 104 recipients transplanted at a single institution, who developed CMV viremia and/or disease, we identified 15 cases of biopsy-proven CMVD and 74 recipients with CMV viremia alone; 30 of 74 were included as control subjects after appropriate surveillance. The rate of CMVD was low at 5%. While patients are monitored for CMV viremia, CMVD was the presenting manifestation of CMV infection in the majority of cases (60%), and 40% did not have viremia at the time of diagnosis. No one risk factor predicted CMVD. Patients with CMVD tended to have high-risk CMV serostatus, moderate to severe graft-versus-host disease, and to have higher mortality rate. Conclusions: Preemptive strategy with targeted therapy to patients with CMV viremia is effective with rare and unpredictable events of breakthrough CMVD. Patients with high-risk CMV serostatus and moderate to severe graft-versus-host disease may need more vigilant observation. Cytomegalovirus disease may occur without viremia requiring close monitoring for symptoms suggestive of CMVD.